Health Personnel’s Practices in Vaccinating Children - Vajanapoom, Nitaya; Wongkraisritong, Wannika; Paopradith, Mayuree (Journal of Health Science of Thailand, 1993)
A cross-sectional study was conducted to investigate the practices in vaccinating children by health personnel from various levels of governmental health services: regional hospitals, general hospitals, provincial medical offices, district hospitals, subdistrict health service centers and health service centers in Bangkok. In October 1989, a total of 2,602 atandardized questionnaires were mailed to the subjects (one at each health service) who were responsible for vaccination of children during May to September 1989. A Total of 1,834 (70.5%) questionnaires were returned. The results showed that 88.3% and 81% of disposable needles including 1.5% and 1.9% of disposable syringes were used when vaccination children in and out of medical sites respectively. Of these, 33% of reusing disposable needles were practiced while giving vaccination in and out of medical sites respectively; and 9% of reusing disposable syringes were found in both sites. The findings also indicated that 17% of reusing disposable syringes were found in both sites. The findings also indicated that 17% of administering vaccinations in medical sites and 21% of those out of medical sites used insufficiently cleaned needles. In addition, 85% of all vaccination in medical sites and 88% of those out of medical sites also used shared-syringes when administering vaccination. It was found that subdistrict health centers had the highest experience of reusing both needles and syringes when vaccinating children, including the use of insufficienly cleaned needles. The number of children sharing was statistically significantly different (P=0.00) between in and out of medical site services in both district hospitals and subdistrict health service centers.